Knowledge and attitudes among preschools staff in Shanghai, China, regarding epilepsy - Qiu, Liyan; Shen, Lixiao; Wang, Junli; Ren, Fang; Xu, Mingyu; Jiang, Fan; Sheng, Xiaoyang; Li, Fei; Li, Feng (BMC pediatrics, 2020)
Background Epilepsy is one of the most common neurological problems among children. The aim of this survey was to assess the knowledge and attitude among preschool staff in Shanghai regarding epilepsy. Methods A cross-sectional survey was carried out among the staff at selected preschools. A stratified random sampling method was first used to identify suitable subjects. Data were obtained using a self-completed questionnaire. A standardized collection of demographic information was performed, and participants were given a questionnaire about their knowledge and attitudes regarding epilepsy. Results A total of 1069 subjects completed the questionnaire. In this survey, 387 (36.2%) staff members had previously participated in related training. 17.6% of teachers knew how to provide appropriate first aid for seizures. Correct responses regarding first aid for seizures, such as laying the person on his or her side (24.9%), moving harmful objects out of the way (20.7%), protecting the head (36.1%), waiting until the seizure ends (7.9%), and dialing the emergency number (40.1%), were low. The staff members had different attitudes towards children with epilepsy: some subjects had a positive attitude, some had a negative attitude. Conclusions The level of first-aid knowledge among preschool staff in Shanghai relevant to epilepsy was low. There is an urgent need to educate staff about epilepsy and appropriate first-aid practices for seizures.